Penerapan Pembelajaran Model Pencapaian Konsep Dengan Pendekatan Kontekstual Untuk Meningkatkan Hasil Belajar Matematika Siswa - D, Zuhri (Jurnal Pilar Sains, 2011)
The effort of increasing result of study and learning effectivity is a main purposeadmired to achieve in every learning process. Because of that, choosing learningstrategy and ability to implement it become important to conduct. In a newparadigm of learning, learning process must be centered on student and it isbegun with context/real problem faced by student in their everyday life. Thepurpose is students are able to see the interconnection of subject they learn withreal condition in their environment. By this approaching, students are hoped toknow the important meaning of what they learn and what it is learnt for, hencethey are highly motivated to study. The contextual approaching foccuses on theimportance of bringing the problem faced by students in their everyday life. Themain problem brought in this research is enhancing the student’s result of studyby implementing concept achievement learning model with contextualappoaching and learning effectivity applied. The research subject is students ofclass VII1 SMPN 3 Minas in year 2007/2008, and design of research used is Onegroup Post Tes Design. Research data are collected by doing a test for student’sresult of study, quetionaire for learning motivation and class observation forteacher and student activities, and organizing of learning. Data analysis used isdescriptive and inferensial statistic analysis. The result of data analysisi resumedthat the emplementation of concept achievement learning model with contextualapproaching could increase the student’s result of study and effective to apply inmathematic learning.